Patients' Experiences of "Long COVID" in the Community and Recommendations for Improving Services: A Quality Improvement Survey - Mohammad Sharif Razai; Roaa Al-Bedaery; Laxmi Anand; Katherine Fitch; Hannah Okechukwu; Teniola M. Saraki; Pippa Oakeshott (SAGE Publishing, 2021)
Introduction: "Long COVID" is a multisystem disease that lasts for 4 or more weeks following initial symptoms of COVID-19. In the UK, at least 10% of patient report symptoms at 12 weeks following a positive COVID-19 test. The aims of this quality improvement survey were to explore patients' acute and post-acute "long" COVID-19 symptoms, their experiences of community services and their recommendations for improving these services. Methods: Seventy patients diagnosed with COVID were randomly selected from 2 large socially and ethnically diverse primary care practices. Of those contactable by telephone, 85% (41/48) agreed to participate in the quality improvement survey. They were interviewed by telephone using a semi-structured questionnaire about community services for COVID-19 patients. Interviews lasted 10 to 15 minutes. Results: Forty-nine percent of patients reported at least 1 post-acute COVID-19 symptom. The most common were severe fatigue (45%), breathlessness (30%), neurocognitive difficulties (such as poor memory), poor concentration and "brain fog" (30%), headaches (20%), and joint pain (20%). Many patients felt isolated and fearful, with scant information about community resources and little safety netting advice. Patients also expected more from primary care with over half (56%) recommending regular phone calls and follow up from healthcare staff as the most important approach in their recovery. Conclusions: In line with patients' requests for more support, the practices now routinely refer patients with long COVID to an on-site social prescriber who explores how they are getting on, refers them to the GP or practice nurse when required, and sign posts them to support services in the community.